2014
DOI: 10.12691/education-2-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of A. hydrophila from the Al-Jadryia River in Baghdad (Iraq)

Abstract: In this paper, we described detection of Aeromonas.hydrophila in water of AL-Jadryia river (Baghdad city, Iraq), during the period from July,2012 to April, 2013. The samples collected from water of Jaderia river and transfer to Bacteriology laboratory for diagnosis. A.hydrophila isolates which were diagnosed by three methods (Culture method, biochemical tests, Api20E system), in Culture method was isolated (71) isolate on blood agar and TCBS media and (44) isolates by biochemical tests while Api20E kit was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The Lip gene was found in Aeromonas isolates at 17.14% [78], while it was highly detected (81.8%) in A. hydrophila strains recovered from diseased Nile tilapia [79]. Meanwhile, some previous studies reported that 100% of A. hydrophila possess hyl and lip genes [60,64,80].…”
Section: Discussionmentioning
confidence: 99%
“…The Lip gene was found in Aeromonas isolates at 17.14% [78], while it was highly detected (81.8%) in A. hydrophila strains recovered from diseased Nile tilapia [79]. Meanwhile, some previous studies reported that 100% of A. hydrophila possess hyl and lip genes [60,64,80].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is consistent with Attia et al [42], who found that a high number of A. hydrophila were positive for the aerA gene (81.8%) and Abd-El-Malek [43] who stated that the percent of lipase in Aeromonas isolates was 17.14%. Contrastingly, a previous study reported that A. hydrophila possesses a high percentage of the hylA gene (100%) [44]. Similarly, A. hydrophila was reported for the presence of hlyA genes (50%) in fish farms in East Delta As observed, the prevalence of A. hydrophila isolates was (65.63%), A. caviae (18.75%) and A. sobria (15.63%).…”
Section: Discussionmentioning
confidence: 63%
“…Smears were taken aseptically using sterile loop from kidney, liver and spleen and streaked to MacConkey agar plates. After streaking the plates were incubated at 37°C for 24 hours following the procedure described in 20 and 16 .…”
Section: Isolation Of Bacteriamentioning
confidence: 99%